Emerging concepts on the mechanical interplay between migrating cells and microenvironment in vivo - Ventura, Guilherme; Sedzinski, Jakub (Frontiers in Cell and Developmental Biology, 2022)
During embryogenesis, tissues develop into elaborate collectives through a myriad of active mechanisms, with cell migration being one of the most common. As cells migrate, they squeeze through crowded microenvironments to reach the positions where they ultimately execute their function. Much of our knowledge of cell migration has been based on cells' ability to navigate in vitro and how cells respond to the mechanical properties of the extracellular matrix (ECM). These simplified and largely passive surroundings contrast with the complexity of the tissue environments in vivo, where different cells and ECM make up the milieu cells migrate in. Due to this complexity, comparatively little is known about how the physical interactions between migrating cells and their tissue environment instruct cell movement in vivo. Work in different model organisms has been instrumental in addressing this question. Here, we explore various examples of cell migration in vivo and describe how the physical interplay between migrating cells and the neighboring microenvironment controls cell behavior. Understanding this mechanical cooperation in vivo will provide key insights into organ development, regeneration, and disease.